Technology Management in Global Competition and Competitive Advantage - Dereli, Deniz Dilara (My University, 2017)
Technology is a major factor for success in the global competitive environment. In today's world, by technological development, competition become more intense and new opportunities arise. Obtaining an advantageous position in the global competitive environment depends on satisfying consumer demands with best quality at an affordable cost. However, achieving and maintaining competitive advantage is not only possible with low cost and high efficiency but also with right technology management. Meeting the changing needs and demands, ensuring competitive advantage and realizing economic growth depends on following technological developments and adapting new technologies to production activities and processes. In this context, it is necessary to understand the relationship between technology and competition, form necessary strategies, realize research and development activities for new technologies, make necessary investments and carry out the process of technology management. Technology management becomes essential for economic growth and sustainability of companies. This study aims to evaluate the impact on competitive advantage of technology management by putting out the importance of technology management.
Keywords: Technology managemet; competition; growth